Civil service and democracy questions in reforming the civil service in eastern and central Europe. - Ridley, F.F. (1995)
"The debate over public service reform is taking place at a time of flux when old models are being challenged everywhere. This article discusses issues of institutional transfer, as between western and east and central Europe, relative to civil service reform and democratisation. It presents several models to describe the place of the civil service in the democratic state and the implications of each for civil service organisation. It argues for a better balance between a legal approach, which tends to dominate advice coming from some continental European countries, and one which emphasises `good' rather than just `correct' relations between administration and citizens. This distinction is fundamental in so far as, under the UK Citizens Charter for example, the citizen is seen as a `customer' rather than a mere `user' of services he has no influence over. The article concludes that, given the differences in culture, political climate and economic situation of `recipient' countries in east and central Europe, each must search for its own reforms, looking for questions rather than answers"
Keywords: Civil service reform - Great Britain; Civil service